Hydrogen-rich syngas production from municipal solid waste gasification through the application of central composite design: An optimization study. (27th November 2020) - Chen, Guanyi; Jamro, Imtiaz Ali; Samo, Saleem Raza; Wenga, Terrence; Baloch, Humair Ahmed; Yan, Beibei; Ma, Wenchao
Abstract: This study aims to investigate the influence and interaction of experimental parameters on the production of optimum H2 and other gases (CO, CO2, and CH4 ) from gasification of municipal solid waste (MSW). Response surface method in assistance with the central composite design was employed to design the fifteen experiments to find the effect of three independent variables (i.e., temperature, equivalence ratio and residence time) on the yields of gases, char and tar. The optimum H2 production of 41.36 mol % (15.963 mol kg-MSW −1 ) was achieved at the conditions of 757.65 °C, 0.241, and 22.26 min for temperature, ER, and residence time respectively. In terms of syngas properties, the lower heating value and molar ratio (H2 /CO) ranged between 9.33 and 12.48 MJ/Nm 3 and 0.45–0.93. The predicted model of statistical analysis indicated a good fit with experimental data. The gasification of MSW utilizing air as a gasifying agent was found to be an effective approach to recover the qualitative and quantitate products (H2 and total gas yield) from the MSW. Graphical abstract: Image 1 Highlights: Hydrogen production from the gasification of MSW was focused. Effect of experimental variables investigated on the MSW conversion. Temperature found as the most influencing experimental parameter. Optimum values of experimental parameters for optimum H2 production were found.